Cultural aspects of resilience from the perspective of households’ everyday practice - Wódz, Kazimiera (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
The subject of the study, the results of which are discussed in this chapter, were the coping strategies of the households affected by the consequences of the 2007–2008 global economic crisis. The research were conducted between years 2014–2017 within the RESCuE Project. In the chapter we refer to the data form one of the thematic reports prepared by the Polish team, focused on the ways in which the cultural resources of the studied households were used in coping with the difficult circumstances, like: job lost, problems with finding the stable employment, death or illness in family, accident leading to severe disability and so on. The selected from the rich empirical material results presented in the chaptershow that the ways the culural and symbolic capital were used in overcoming the consequences of crisis by the respondendent living in Upper Silesia and Zagłębie Dabrowskie are very similar indepenendly of the place where the research was carried.